Галузевий аспект промислової політики в умовах Індустрії 4.0 та 5.0 (на прикладі приладобудування) - Omelyanenko, Vitaliy A. (Institute of Industrial Economics of NAS of Ukraine, 2025)
The article is devoted to the consideration of the features and global trends of the development of the instrumentation engineering industry and the main ideas for industrial policy for its development in the context of the transition to Industry 4.0 and 5.0. The basic global models of the development and projects in instrumentation engineering industry are determined. Recommendations for industrial policy in the field of instrumentation engineering industry in Ukraine are formulated.